LongLLaDA: Unlocking Long Context Capabilities in Diffusion LLMs - Liu, Xiaoran; Song, Yuerong; Liu, Zhigeng; Huang, Zengfeng; Guo, Qipeng; He, Ziwei; Qiu, Xipeng (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Large Language Diffusion Models, or dLLMs, have emerged as a significant focus in NLP research, with substantial effort directed toward understanding their scalability and downstream task performance. However, their long-context capabilities remain unexplored, lacking systematic analysis or methods for context extension. In this work, we present the first systematic investigation comparing the long-context performance of diffusion LLMs and traditional auto-regressive LLMs. We first identify a unique characteristic of dLLMs, unlike auto-regressive LLMs, they maintain remarkably ***stable perplexity*** during direct context extrapolation. Moreover, where auto-regressive models fail outright during the Needle-In-A-Haystack task with context exceeding their pretrained length, we discover dLLMs exhibit a distinct ***local perception*** phenomenon, enabling successful retrieval from recent context segments. We explain both phenomena through the lens of Rotary Position Embedding (RoPE) scaling theory. Building on these observations, we propose LongLLaDA, a training-free method that integrates LLaDA with the NTK-based RoPE extrapolation. Our results validate that established extrapolation scaling laws remain effective for extending the context windows of dLLMs. Furthermore, we identify long-context tasks where dLLMs outperform auto-regressive LLMs and others where they fall short. Consequently, this study establishes the first length extrapolation method for diffusion LLMs while providing essential theoretical insights and empirical benchmarks critical for advancing future research on long-context diffusion LLMs.